A balanced transcription between telomerase and the telomeric DNA-binding proteins TRF1, TRF2 and Pot1 in resting, activated, HTLV-1-transformed and Tax-expressing human T lymphocytes - Escoffier, Emmanuelle (BioMed Central, 2005)
BACKGROUND: The functional state of human telomeres is controlled by telomerase and by a protein complex named shelterin, including the telomeric DNA-binding proteins TRF1, TRF2 and Pot1 involved in telomere capping functions. The expression of hTERT, encoding the catalytic subunit of telomerase, plays a crucial role in the control of lymphocyte proliferation by maintaining telomere homeostasis. It has been previously found that hTERT activity is down-regulated by the human T cell leukaemia virus type 1 (HTLV-1) Tax protein in HTLV-1 transformed T lymphocytes. In this study, we have examined the effects of Tax expression on the transcriptional profile of telomerase and of shelterin in human T lymphocytes. RESULTS: We first provide evidence that the up-regulation of hTERT transcription in activated CD4+ T lymphocytes is associated with a down-regulation of that of TERF1, TERF2 and POT1 genes. Next, the down-regulation of hTERT transcription by Tax in HTLV-1 transformed or in Tax-expressing T lymphocytes is found to correlate with a significant increase of TRF2 and/or Pot1 mRNAs. Finally, ectopic expression of hTERT in one HTLV-1 T cell line induces a marked decrease in the transcription of the POT1 gene. Collectively, these observations predict that the increased transcriptional expression of shelterin genes is minimizing the impact on telomere instability induced by the down-regulation of hTERT by Tax. CONCLUSION: These findings support the notion that Tax, telomerase and shelterin play a critical role in the proliferation of HTLV-1 transformed T lymphocytes.